Sekolah sebagai Ruang Pembentukan Karakter dan Kesadaran Sosial - Beni Chandra Purba (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Schools are positioned as strategic social spaces that play a crucial role in shaping students’ character and social awareness amid the growing complexity of educational challenges in the era of globalization, digitalization, and shifting social values. An educational orientation that continues to prioritize academic achievement has generated serious issues, including the weakening of character, low levels of empathy, and declining social concern among students. The research problem addressed in this study concerns how schools can fulfill their function not only as institutions for knowledge transmission, but also as spaces for the sustainable formation of values, attitudes, and social responsibility. This study aims to analyze the role of schools as arenas for character formation and social awareness, as well as to identify relevant educational approaches for internalizing moral, ethical, and social values. A qualitative approach was employed through a literature review with descriptive analysis of scholarly publications, educational policies, and character education practices. The findings indicate that schools function effectively as educational social environments when character values are systematically integrated through the curriculum, pedagogical interactions, school culture, extracurricular activities, and teacher role modeling. Character formation and social awareness become more meaningful when implemented holistically, contextually, and consistently. The conclusion emphasizes that schools bear moral and social responsibility to create a humanistic, participatory educational ecosystem oriented toward the development of students’ holistic personality. The novelty of this scholarly work lies in its conceptual affirmation of the school as a transformative social space that unifies academic dimensions, character development, and social awareness into an inseparable pedagogical whole.